(untitled) (Ameghiniana, 2014)
The present paper deals with a benthonic foraminiferal fauna, Uppermost Valanginian to Lower Hauterivian in Age. In this presumably euhaline shallowepineritical association thirteen species, mainly nodo oarians, are recognized. Most of the species are included in geographically well-distributed taxa. Marginulinopsis picunleufuensis tenuistriata nov. subsp. is proposed